2019
DOI: 10.1177/0310057x19853593
|View full text |Cite
|
Sign up to set email alerts
|

A balancing act: The Supervisor of Training role in anaesthesia education

Abstract: In this qualitative study, we report how Supervisors of Training, educational supervisors overseeing the learning of anaesthesia trainees, experience their role in practice. Using purposive sampling, we interviewed Supervisors of Training from across Australia and New Zealand. The interviews began by asking ‘what do you see as your role as a Supervisor of Training?’ then explored the response in detail. Following the technique of thematic analysis, inductive analysis occurred as data were collected until we ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A further step would be granting trainees some control over the selection of performance information presented to inform progress decisions, which has been associated with the successful implementation of assessment for learning in an undergraduate setting 1,13 . We anticipate this last measure will be contentious in postgraduate contexts such as ours, where supervisors feel an obligation to their community to ensure the quality of graduating specialists 53 . However, these options we have presented are not prescriptions but serve to highlight the role assessment design decisions may have in how assessments are used in practice; we would encourage designers of assessment systems to consider these or other features tailored to their individual contexts, which may enhance trainee trust and hence encourage assessment for learning in WBA.…”
Section: Discussionmentioning
confidence: 99%
“…A further step would be granting trainees some control over the selection of performance information presented to inform progress decisions, which has been associated with the successful implementation of assessment for learning in an undergraduate setting 1,13 . We anticipate this last measure will be contentious in postgraduate contexts such as ours, where supervisors feel an obligation to their community to ensure the quality of graduating specialists 53 . However, these options we have presented are not prescriptions but serve to highlight the role assessment design decisions may have in how assessments are used in practice; we would encourage designers of assessment systems to consider these or other features tailored to their individual contexts, which may enhance trainee trust and hence encourage assessment for learning in WBA.…”
Section: Discussionmentioning
confidence: 99%
“…However, the insider lacks the fresh perspective that an outsider may bring to a line of enquiry. 14 As such, EP and VB were included as ‘outsiders’. They are both emergency physicians with backgrounds in anthropology and medical education, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Supervisors have reported that they find it challenging to have feedback conversations with trainees when the observed activity is seen to be below-par, or if a series of observed events have been viewed to be sub-standard ( 36 ). Supervisors not only report the emotional burden they feel after engaging in these discussions ( 37 ), but observational studies of feedback show that supervisor language in these conversations takes on a distinctive tenor – what some have reported as “vanishing” ( 38 ), others as “mealy mouthed” ( 39 ), and others as “hesitant and apologetic.” Johnson and Molloy ( 40 ) describe how supervisors talk in circles in an attempt to diminish the negative emotional impact on learners.…”
Section: Troubling the Intersections Of Feedback And Underperformance...mentioning
confidence: 99%